EVALUASI DAMPAK KEBIJAKAN SEKOLAH GRATIS TERHADAP MUTU PENDIDIKAN DI SMPN 10 BENGKULU TENGAH - Henny Aprianty; Erriyanto, Erriyanto; Alexsander (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
This research was conducted with the aims of: 1) identifying and understanding the impact of implementing the free education policy on community response; 2) How is the impact of implementing a free education policy perceived and understood on students, teachers and objectives? 3) How to identify and understand the impact of implementing free education policies on student motivation and teacher performance? 4) How to see and understand the impact of implementing the free education policy on the student population? national exam results). The type of research used in this research is qualitative research. This research uses a descriptive evaluation research method using the CIPP (Context, Input, Process, Output) model. This research data was obtained from primary and secondary data. Data collection methods include observation methods, interview methods, and written methods. Data analysis techniques use data reduction, data visualization, and inference/verification. The results of this research are as follows. 1) Regarding facilities, there are still financial obstacles that the Bengkulu government has not been able to overcome. Of course, free school programs don't live up to their name because they aren't truly free. 2) In terms of process, apart from that, the time lag between the process of measuring and distributing shoes, which takes quite a long time while students continue to develop physically, means that the shoe size is no longer appropriate. 3) In context/output, the output of the Free School Program at SMPN 10 Central Bengkulu Regency still requires improvement, because deficiencies are still being discovered. 4) In terms of impact, the Free School Program has shown an impact on increasing school enrollment rates (APS) at SMPN 10 Central Bengkulu Regency. In effect, the student's parent's family can divert funds that should be used for education to other needs.